THE EFFECT OF ENVIRONMENT DIMENSIONS OF CONTINGENCY ON BUDGETARY SLACK - Andi Ayu Frihatni; Ahmad Abbas (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research aims at testing the effect of contingency determinants dimensioned into organizational commitment, budgeting participatory, information asymmetry and environmental uncertainty on the budgetary slack. The sample of this research is sixty governmental internal auditors of BPKP in South Sulawesi. All data were analyzed using path analysis. The results have shown that contingency determinants consisting of organizational commitment, budgeting participatory, information asymmetry, and environmental uncertainty provide positive direct effect on the budgetary slack, otherwise organizational commitment has no indirect effect on the relationship between contingency determinants and the budgetary slack